Metal oxide nanoparticles as a promising method to reduce biotic stress in plant cell wall: A review - Yalew Yiblet; Miseganaw Sisay (Heliyon)
The application of metal-based nanoparticles in inhibiting plant pathogenic bacteria and fungi has gained significant attention in recent years. several nanoparticles, including silver (Ag), titanium dioxide (TiO2), magnesium oxide (MgO), copper (Cu), and zinc oxide (ZnO), can generate reactive oxygen species (ROS) when exposed to light. The oxidative damage inflicted by ROS can disrupt the cellular structures and metabolic processes of pathogens, leading to their inactivation and inhibition. However, it is crucial to consider the potential environmental and health impacts of nanoparticle use. The safe and responsible use of nanoparticles and their potential risks should be thoroughly evaluated to ensure sustainable and effective plant disease management practices.